STEFANYK’S PORTRAIT OF EMIGRANT (To the 100-th anniversary of Ukrainian settlement in Canada: 1891-2011) - Rozumny, Y. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article highlights the problem of artistic representation of migrant’s image in V. Stefanyk’s short stories. The work is timed to 120 anniversary of Ukrainian settlement in Canada, the 1891-2011.